Early results of rapid-deployment aortic prosthesis in multivalvular surgery – a propensity score matching. (3rd October 2022) - Carvalho Guerra, N; Velho, T; Pereira, R M; Reis, I; Nobre, A
Abstract: Background: Multivalvular surgery (MV) requires prolonged extracorporeal circulation (ECC) and aortic cross-clamp times (X-Ao). Rapid-deployment aortic prosthesis (RD-AV) allow lower ECC and X-Ao times in isolated aortic valve surgery (AVR), but have not been studied in MV surgery. Purpose: To determine if RD-AV use influences early outcomes when compared to biological stented or mechanical aortic valves in MV surgery. Methods: Retrospectively collected pre, intra and immediate post-operatory data on all MV adult patients with AVR operated on our Department from January 2016 to February 2022. Bentall surgery and aortic dissection patients were excluded. A propensity score matching (PSM) of patients receiving RD-AV (Group A) compared to patients with non-RD-AV (Group B) was performed using sex, age, Euroscore II, type of surgery (involved valves, CABG, ascending aortic replacement), active endocarditis, ventricular function and redo surgery. After PSM, we compared outcomes until death or discharge. Normal distribution of samples was tested using the Kolmogorov-Smirnov test. Normal data was analysed with unpaired t-testing and non-normal data with non-parametric Mann Whitney U test. Categorical data were analysed with Fisher test. A significance level of p<0.05 was accepted. Results: 205 patients received non-RD-AV and 58 patients RD-AV. After PSM, 57 pairs of patients were obtained. Sex, BMI, Euroscore II, age, redo surgery, insulin dependent DM, baseline creatinine, left ventricle ejection fraction, right ventricle dysfunction, pulmonary artery systolic pressure, and active endocarditis were similar in both groups. Intra-operatory, RD-AV valves (Group A) were associated with shorter surgery duration (167.3±52 vs 206.6±91 min, p=0.005), shorter ECC duration (89.5±36.5 vs. 118.9±56.5 min, p=0.002), and aortic X-clamp time (71.6±28 vs. 98.9±38.2 min, p<0.001). No differences were found between both groups A vs. B in ventilation time (1270±1911 vs. 2428±5627 min, p=0.59), inotropic support (113±178 h vs. 85±101 h, p=0.38), transfusion of red cells units (1.1±1.6, vs. 1.2±1.7, p=0.73), Fresh frozen plasma units (0.86±1.9, vs. 0.77±1.8, p=0.77), platelet pools (0.79±1.0 vs. 0.7±0, 9, p=0.67), fibrinogen (0.77±1.5 vs. 0.75±1.4 g, p=0.98), intra-aortic balloon pump use (5 vs. 12 patients, p=0.11), chest drain output (804±656 vs. 825±992 ml, p=0.69), new-onset dialysis (10 vs. 10 patients, p=1.0), new-onset atrial fibrillattion (10 vs 13 patients, p=0.6) and permanent pacemaker implantation (8 vs. 3 patients, p=0.20). Total ICU stay (9.25±21 vs. 4.5±4 days, p=0.3), hospital stay (14.4±26 vs. 10.1±13 days, p=0.52) and intra-hospital mortality (7 vs 9 patients, p=0.79) were also similar. Conclusion: Despite shorter surgery duration, ECC duration and aortic X-clamp duration, RD-AV have similar early outcomes when compared with non-RD-AV in multivalvular surgery. Funding Acknowledgement: Type of funding sources: None.